Lung Metastases in Newly Diagnosed Esophageal Cancer: A Population-Based Study - Guo, Jida; Zhang, Shengqiang; Li, Huawei; Hassan, Mohamed Osman Omar; Lu, Tong; Zhao, Jiaying; Zhang, Linyou (Frontiers in Oncology, 2021)
As we all know, Esophageal cancer (EC) is one of the most common cancers, and the lung is its common distant metastatic site. However, population-based based data on the proportion and prognosis of esophageal cancer with lung metastases (ECLM) at the newly diagnosis is currently lacking.The population of this study was obtained from the Surveillance, Epidemiology, and End Result (SEER) database from 2010 to 2016. Multivariable logistic were performed to identify predictors of the presence of ECLM at diagnosis, Multivariable Cox regression and competing risks analysis was used to assess the prognostic factors in esophageal cancer patients with lung metastasis (LM). A total of 713 (6.50%) patients with initial lung metastasis were diagnosed from among 10 965 patients with esophageal cancer from 2010 to 2016, and the lung metastasis patients accounted for 27.15% of the subset with metastatic disease to any distant site. Among the entire cohort, multivariable logistic regression determined pathology grade, pathology type, T staging, N staging, race, number of extrapulmonary metastatic sites six factors as predictive factors of the presence of lung metastases at initial diagnosis. The median survival time of ECLM patients was 4.0 months. Patients receiving chemotherapy or chemotherapy plus radiotherapy had the longest median overall survival, the median survival of both them was 7.0 months. Multivariable Cox regression confirmed age, histology type, T2 staging, number of extrapulmonary metastatic sites, treatment （chemotherapy, radiotherapy, chemotherapy plus radiotherapy）five factors as independent predictors for overall survival (OS), and multivariable competing risks analysis determined age, number of extrapulmonary metastatic sites, treatment three factors as independent predictors for esophageal cancer-specific survival (CSS). This study revealed the population-based analysis of the proportion and prognosis for LM at the time of EC diagnosis. The findings of this study might provide the basis of diagnosis ECLM earlier and appropriate treatment choices for the patients.